Race and the making of the Mormon people - Mueller, Max Perry (The University of North Carolina Press, 2017)
"Max Perry Mueller argues that the nineteenth-century history of the Church of Jesus Christ of Latter-day Saints illuminates the role that religion played in the formation of the notion of the three 'original' American races--'red,' 'black,' and 'white'--for both Mormons and others in the Intermountain West. Notably recovering the voices of a handful of black and Native American Mormons who persistently wrote themselves into the Mormon archive, Mueller threads together historical experience and scriptural hermeneutics, finding that the Book of Mormon is key to understanding how early Mormons both departed from and reflected antebellum conceptions of race as biblically and biologically predetermined. Mormon thought both challenged and reaffirmed the essentialist nature of the racialized American experience"--